Concept of the Separation of Powers: A Look from the Shariah Point of View - Abubakar, Yusuf Sani; Dorloh, Sulaiman; Haji Aji, Rajali (International Journal of Scientific Research and Management (IJSRM), 2024)
The separation of powers is the division of the government of a state into different branches, each with its own independent powers. The purpose of a system of separation of powers is to prevent the concentration of power by providing checks and balances. This paper aims to investigate this concept from the Shariah point of view. To achieve this, the research adopts a qualitative research methodology. It is found that the principle of the separation of powers in Islamic Shariah was not clearly present at the time of the Prophet (S.A.W), as he held all three powers. After the Prophet's (S.A.W) death, the principle became clearer in the era of the caliphate, especially in the era of Caliph Omar ibn al-Khattab, who separated the judicial authority from the other state powers.  However, the books of Islamic history are full of examples showing that the judges throughout the territory of the Islamic caliphate worked without interference from the rulers, even the rulers themselves were appointed by the judges and appeared before the courts. From such examples, the idea of the separation of powers has been derived.